Community-Based Ecotourism in Strengthening Local Empowerment: A Case Study of Umbul Manten, Sidowayah Village, Polanharjo District, Klaten - Nur Hayati, Beti (IJTIMAIYA: Journal of Social Science and Teaching, 2026)
Community-based tourism has become an important approach to promoting sustainable tourism while improving local community welfare. This study analyzes the implementation of community-based ecotourism in strengthening local empowerment in the management of Umbul Manten tourism, Klaten Regency. The research uses a qualitative case study approach through observations, in-depth interviews, and documentation. The findings show that the management of Umbul Manten by the Village-Owned Enterprise (BUMDes) and local communities reflects the principles of community-based ecotourism through environmentally oriented management, active community participation, and the development of local economic activities. Environmental conservation is carried out by preserving spring water sources, maintaining surrounding vegetation, and implementing environmental protection regulations. Community involvement also contributes to employment opportunities, diversification of local businesses, and stronger participation in tourism development. Overall, the study demonstrates that community-based ecotourism supports environmental sustainability, local empowerment, and economic development simultaneously.